2011
DOI: 10.4269/ajtmh.2011.11-0086
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Measures of Immune Complex and Complement Function and Immune Complex–Mediated Granulocyte Activation in Human Lymphatic Filariasis

Abstract: The presence of circulating immune complexes (CICs) is a characteristic feature of human lymphatic filariasis. However, the role of CICs in modulating granulocyte function and complement functional activity in filarial infection is unknown. The levels of CICs in association with complement activation in clinically asymptomatic, filarial-infected patients (INF); filarial-infected patients with overt lymphatic pathologic changes (CPDT); and uninfected controls (EN) were examined. Significantly increased levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Other studies suggested that AEs may be related to circulating immune complexes (CICs) that form when filarial antigens are released by dying parasites [ 16 , 17 ]. CICs from plasma of LF-infected individuals have been shown to be proinflammatory when added to granulocytes [ 18 ]. A recent clinical trial provided us with the opportunity to use 21st-century methods to revisit the issue of AE pathogenesis.…”
mentioning
confidence: 99%
“…Other studies suggested that AEs may be related to circulating immune complexes (CICs) that form when filarial antigens are released by dying parasites [ 16 , 17 ]. CICs from plasma of LF-infected individuals have been shown to be proinflammatory when added to granulocytes [ 18 ]. A recent clinical trial provided us with the opportunity to use 21st-century methods to revisit the issue of AE pathogenesis.…”
mentioning
confidence: 99%
“…however, each of these assays uses some unique characteristic of immune complexes such as complement opsonization for quantification and their clinical significance is not well established (Van Hoeyveld and Bossuyt, 2000). Concentration of immune complexes in circulation of normal human individual ranges between 2.3 μg/mL (Senbagavalli et al, 2011) and 5 μg Eq/mL (Quidel, MicroVue, CIC-RAJI EIA, Cat # A002) depending on the method used. Therefore, IC may be present in circulation of normal individuals without causing disease, indicating steady state clearance of foreign or abnormal antigens.…”
Section: Tablementioning
confidence: 99%
“…Senbagavalli et al . have shown that high levels of circulating antigen, in combination with antigen‐specific antibodies, activate the complement system in asymptomatic persons, whereas the reduced status of complement activity in patients with chronic pathologic changes may aggravate disease morbidity . Studies in murine models suggest the involvement of both the Th1 and Th2 arms of immunity in resistance to filarial parasites .…”
Section: Molecular Mechanisms Underlying Lymphatic Filariasis Progresmentioning
confidence: 99%